Space and the city: Gender identities in the seventeenth-century Norwich - WILLIAMSON, Fiona (Institutional Knowledge at Singapore Management University, 2012)
Influenced by interdisciplinary studies and the ‘spatial turn’ in social history, this article explores the relationship between space and the construction of gender identity amongst the poor to middling sorts of seventeenth-century Norwich. To this end I have considered gendered interaction in different ‘types' of space: domestic, private space, ‘borderline’ space – such as the alehouse or threshold – and, finally, the public space of streets and markets. Each section explores the relevance of recent spatial historiography in the Norwich context, and evaluates whether men and women inhabited different ‘worlds' in the city, not only in terms of their physical movement or access to certain places but also, more importantly, in terms of how their presence was perceived, and thus their identity shaped by others. The empirical basis is primarily defamation depositions of the Norwich Diocese Court, largely used by the middling sorts, contextualized where appropriate with secular court records.